Science and technology of rubber - Mark, James E., 1934-; Erman, Burak (Amsterdam ; Boston : Elsevier Academic Press, 2005)
The 3rd edition of The Science and Technology of Rubber provides a broad survey of elastomers with special emphasis on materials with a rubber-like elasticity. As in the 2nd edition, the emphasis remains on a unified treatment of the material; exploring topics from the chemical aspects such as elastomer synthesis and curing, through recent theoretical developments and characterization of equilibrium and dynamic properties, to the final applications of rubber, including tire engineering and manufacturing. Many advances have been made in polymer and elastomers research over the past ten years since the 2nd edition was published. Updated material stresses the continuous relationship between the ongoing research in synthesis, physics, structure and mechanics of rubber technology and industrial applications. Special attention is paid to recent advances in rubber-like elasticity theory and new processing techniques for elastomers. This new edition is comprised of 20% new material, including a new chapter on environmental issues and tire recycling. Explores new applications of rubber within the tire industry, from new filler materials to green tires (a tire that has yet to undergo curing and vulcanization). 30% of the material has been revised from the previous edition with the addition of 20% new material, including a chapter on the environment. A mixture of theory, experiments, and practical procedures will offer value to students, practitioners, and research & development departments in industry.
Rubber elasticity : basic concepts and behavior / A.N. Gent -- Polymerization : elastomer synthesis / Roderic P. Quirk and Deanna L. Gomochak Pickel -- Structure characterization in the science and technology of elastomers / C.M. Roland -- The molecular basis of rubberlike elasticity / Burak Erman and James E. Mark -- The viscoelastic behavior of rubber / K.L. Ngai and Donald J. Plazek -- Rheological behavior and processing of unvulcanized rubber / James L. White -- Vulcanization / Aubert Y. Coran -- Reinforcement of elastomers by particulate fillers / Jean-Baptiste Donnet and Emmanuel Custodero -- The science of rubber compounding / Brendan Rodgers and Walter Waddell -- Strength of elastomers / A.N. Gent -- The chemical modification of polymers / A.F. Halasa, Jean Marie Massie, and R.J. Ceresa -- Elastomer blends / Sudhin Datta -- Thermoplastic elastomers / Brian P. Grady and Stuart L. Cooper -- Tire engineering / Brendan Rodgers and Walter Waddell -- Recycling of rubbers / Avraam I. Isayev.
Includes bibliographical references and index.
Keywords: Rubber; Caoutchouc; Electronic books